Depositional Environment Characteristic of The Late Miocene Kerek Formation in Kendeng Basin: A Case from Cipluk Area, Kendal Regency, Central Java - Joseph Emmanuel Ardine; Septyo Uji Pratomo; Carolus Prasetyadi; M. Ocky Bayu Nugroho; Aga Rizky; Yohanes Citra Kristanto; I Nyoman Agus Dharma Manggala (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
This study focused on the Late Miocene Kerek Formation in Cipluk, Kendal Regency, Central Java, which belongs to the Kerek Formation, a lithostratigraphy unit characterized by Early Miocene - Late Miocene turbidite deposits. The research aims to comprehensively interpret the depositional environment characteristics of the Late Miocene Kerek Formation based on lithofacies, thin section analysis, and micropaleontological analysis. Gaining insights into facies characteristics and the depositional environment will offer novel perspectives for the exploration and development of oil and gas resources in the Kendeng basin. The methodology consists of data collection, analysis, and synthesis. Results indicate that the study area is dominated by classical turbidite facies, suggesting a distal zone with slow sediment settling. The analysis reveals that the Late Miocene Kerek Formation was deposited in a deep marine environment within the inner bathyal—outer bathyal bathymetry zone, specifically in the lower fan section of a submarine fan system. Based on the characteristics of existing deposits and facies, the deposition environment is identified as a fine-grained, mud-rich complex in an elongated submarine fan. These findings contribute to a better understanding of the Late Miocene depositional environment in the Kendeng Basin, Central Java.